The Conception of Personality in the Philosophy of Neo-Thomism - Kuzmickas, Bronius (Problemos, 1969)
The scholastic formula, propounded by the Catholic philosopher Thomas Aquinas, treats personality as an individual substance of rational nature. The formula makes the theoretical basis of the neo-Thomistic understanding of personality. The author attempts to show the real problems reflected in the neo-Thomistic understanding of personality. The article speaks of the linking points between neo-Thomism and contemporary irrationalistic philosophy. A critical evaluation of the neo-Thomistic understanding of the interrelation between personality and society is given in the paper.